Morton Smiths fortolkning af Jesus - Bilde, Per (Religionsvidenskabeligt Tidsskrift, 1999)
<p class="MsoNormal" style="margin: 0cm 0cm 0pt 14.2pt; text-align: justify; mso-pagination: widow-orphan; tab-stops: 0cm 14.2pt 28.4pt 42.65pt 56.85pt 71.1pt 85.3pt 99.5pt 113.75pt 127.95pt 142.2pt 156.4pt 170.6pt 184.85pt 199.05pt 213.3pt 227.5pt 241.7pt 255.95pt 270.15pt 284.4pt 298.6pt 312.8pt 327.05pt;">The purpose of this small article is to present Morton Smith’s book, Jesus the Magician (1978a), seen in the context of his other writings. As well as that, Morton Smith’s book is related to some of the more significant contributions to the quest for the historical Jesus in the 1980s and 1990s. Generally, my evaluation of Morton Smith’s book is positive.